Association between Flash Glucose Monitoring and Metabolic Control as well as Treatment Satisfaction in Outpatients With Diabetes Type 1 - Kramer, Guido; Michalak, Laura; Müller, Ulrich Alfons; Kloos, Christof; Werner, Christoph; Kuniss, Nadine (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective The aim of this study was to follow-up people with diabetes type 1 and Flash Glucose Monitoring (FGM) regarding metabolic control and treatment satisfaction.Methods 40 people with diabetes type 1 and FGM use of ≥6 months were included in the study (female 55%, age 50.9 y, diabetes duration 21.9 y, HbA1c 7.4%, 57.6 mmol/mol, insulin pump therapy 32.5%). The number of scans per day and time/frequency of hypoglycaemia (interstitial glucose value ≤3.9 mmol/l) was recorded from 28 days of the glucose readings. Change of treatment satisfaction was assessed with the DTSQc questionnaire at follow-up (range−18 to+18).Results Mean time of follow-up was 1.0±0.4 y. At follow-up, all participants scanned interstitial glucose 11.9±7.7 times/day. Number of self-monitoring of blood glucose decreased from 6.7±4.2 (baseline) to 0.9±1.8 (follow-up) per day (p<0.001). In individuals with baseline HbA1c ≤7.5%, HbA1c increased (from 6.6±0.7% to 7.0±0.4%, p=0.020). On the contrary, in people with HbA1c>7.5%, HbA1c decreased (from 8.2±0.7% to 7.8±0.7%, p=0.001). In all participants, there were no differences regarding insulin dosage (33.8±12.9 vs. 34.6±13.9 IU/day, p=0.679) and number of insulin injections/day (3.9±2.3 vs. 4.0±2.6, p=0.813) between baseline and follow-up. Frequency of symptomatic hypoglycaemia was at baseline 0.3±0.3 events/day and 0.48±0.36 events/day (recognised, symptomatic events) at follow-up, respectively. In addition, 0.26±0.21 unrecognised hypoglycaemic events/day occurred at follow-up. Treatment satisfaction increased by+12.6 points.Conclusions FGM was associated with an enormous increase in treatment satisfaction and slightly improved metabolic control in people with baseline HbA1c>7.5%. The number of capillary glucose measurements decreased significantly.
Keywords: flash glucose monitoring; type 1 diabetes; freestyle libre